ANALISIS PENGUKURAN ULANG TONAGE KAPAL PENANGKAP IKAN DENGAN PANJANG KURANG DARI 24 METER - Bambang Sudjasta; Purwo Joko Suranto; Chinatha Erwin Sandika Putra (Bina Teknika, 2018)
This research was conducted to know the change of Gross Tonnage (GT) size of fishing vessels before and after re-measurements by measuring experts appointed according to the Ministerial Regulation of the Ministry of Transportation Year 2013 on Ship Measurement, as well as calculating the expected revision of Non-Tax State Revenue (PNBP). Data processing using SPSS program, one of which is paired sample T-test is a test that can compare data before and after data. Tests paired sample T-test has a requirement, that the data must be normally distributed, then the kolmogorov smirnov normality test to determine the normal distribution data or not. The result of kolmogorov sminov test concluded normal distributed data and can be tested paired sample T-test. From result of paired sample T-test is known comparison of data have real difference. Then the analysis of this research was done and resulted some conclusion that difference of GT increase equal to 73% before before measurement, PNBP assumed can accept new income equal to Rp. 3,458,304,- for port services, and navigation services Rp. 11.376.000,- if calculated one week ship only operate one time and for one year.